Global Competence Development in Dual Vocational Education and Training: A Comparative Analysis of Spain and China’s Implementation Strategies - Yue, Luan (Journal of Research in Vocational Education, 2025)
This study examines the development of global competence within Dual Vocational Education and Training (Dual VET) systems through a comparative analysis of Spain and China’s implementation strategies. As globalization intensifies demand for internationally competent technical professionals, vocational education systems must adapt to cultivate students’ intercultural communicative competency, technical proficiency, collaborative ability, and global awareness. Spain’s Dual VET system, integrated within European Union frameworks since 2012, demonstrates systematic approaches to global competence development through competency-based curricula, multilevel progression structures, multi-stakeholder governance models, and extensive international workplace training opportunities. In contrast, China’s Dual VET implementation, despite over forty years of German model adaptation, remains primarily project-based with limited systematic coverage and government-dominated governance structures. Through comparative analysis across legal frameworks, social partner involvement, curriculum design, and international mobility mechanisms, this research identifies key success factors from Spain’s experience and examines their transferability to China’s context. The findings reveal that effective global competence development requires systematic integration rather than isolated interventions. Strategic recommendations for China include developing competency-based standards, establishing balanced industry-education collaboration councils, and implementing comprehensive international mobility frameworks through regional pilots. This study contributes to international discourse on Dual VET globalization by demonstrating adaptation strategies that preserve institutional integrity while leveraging proven international practices for enhanced global competence development.